(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the frequency of in-hospital mortality in patients with acute ST-Elevation Myocardial Infarction complicated with ventricular septal rupture. Study Design: Descriptive Cross sectional study Place and Duration of Study: This study was conducted at the Cardiology department, NICVD, Karachi, Pakistan from March 26, 2021 to September 25, 2021. Methods: All patients who visited the NICVD Karachi and met the eligibility requirements were included in the study. All the patients were assessed for ventricular septal rupture secondary to STEMI. Post STEMI patients were followed for one week to assess in hospital mortality. All data collected were entered into the attached form and used electronically for research purposes. Results: Mean ± SD of age was 57.2±11.5 years. In distribution of gender, 39 (68.4%) were male while 18 (31.6%) were female. In-hospital mortality was found to be in 16(28.1%) patients. Conclusion: In conclusion, VSR, a condition affecting patients, requires accurate clinical judgment and ECG to quickly diagnose and determine the most suitable treatment at the appropriate time, depending on the patient's condition.